A global/local approach for the prediction of the electric response of cracked solar cells in photovoltaic modules under the action of mechanical loads. (December 2016) - Paggi, M.; Corrado, M.; Berardone, I.
Highlights: Global/local finite element approach to fracture in solar cells embedded in PV modules. Multi-physics simulation of the coupling between mechanical and electric fields. Model parameters identification based on experimental data from electroluminescence tests. Abstract: A numerical approach based on the finite element method to assess the impact of cracks in Silicon solar cells on the electric response of photovoltaic modules is proposed. A global coarse-scale finite element model of the composite laminate is used for carrying out the structural analysis. The computed displacements at the edges of each solar cell are passed via a projection scheme as boundary conditions to a 3D local fine-scale finite element model of the cells which accounts for cohesive cracks. The evaluated crack opening displacements along the crack faces are finally used as input to an electric model characterizing the grid line/solar cell ensemble. The identification of the relation between the localized electric resistance due to cracks and the crack opening, to be used as a constitutive model of cracks, is finally discussed in reference to experimental tests performed in the laboratory.